(untitled) (MIST International Journal of Science and Technology, 2020)
In satellite communication, Link Budget analysis is the most important part to determine gains and losses of signals from the transmitter to the receiver. Most importantly, it investigates system performance and optimum power which must be received at the receiver channel. In some cases, this information could be generated, saved for past data analysis, and share with peer users which are not found in existing web tools. Thus, it is obvious to design a new Link Budget calculator with users, database, and data retrieval support. This work focuses on designing a Link Budget web tool for X-band satellite communication through literature study and comparative analysis. The X-Band calculator is designed based on HTML, PHP, Javascript, and MySQL by ensuring several security issues, and can be accessed through mobile devices. This paper also focuses on the necessary equations of Link Budget for Uplink (Tx); Satellite; Downlink (Rx); Azimuth, Elevation, Distance analysis; and Rain attenuation. Though, comparative assessments among various web tools show some fluctuations, overall outputs show satisfactory results with small % of Errors (PoE) ensuring reliability and viability of the proposed X-Band tool for practical use.